Evaluation of the Biomass of the Green Oak (Quercus Rotundifolia) of the Central Middle Atlas: Case of the South Jbel Aoua Forest (Morocco) - EL MDERSSA, Mohamed; BENJELLOUN, Hassan; ZENNOUHI, Omar; NASSIRI, Laila; IBIJBIJEN, Jamal (Journal of Forests, 2018)
The present study is carried out on the green oak forest of Jbel Aoua South, in the Central Middle Atlas. The objective of this work is to estimate the dry biomass of these stands while characterizing this zone in terms of soil and floristic potential. According to the results obtained, the estimated biomass production is 42,70t/ha, based on 30 sample trees using the dimensional analysis method, or an energy equivalent of 192.15106 kcal/ha, which represents a potential income of 3260 to 3586 DH/ha/year. The forage value of the green oak in the forest of Jbel Aoua South is 372 FU/ha. The soil studied is of the para-rendzine carbonate type with a sandy loamy texture, rich in potassium and moderately low in phosphorus.